Curcumin Protective Potential for the Seminiferous Tubules of Mice Treated with Lead Acetate - Undaryati, Yeti Mareta; I’tishom, Reny; Sudjarwo, Sri Agus (Trends in Sciences, 2023)
Curcumin as an antioxidant plays an important role in reducing lead toxicity. This research aimed to demonstrate the potential of curcumin in maintaining epithelial thickness and diameter of seminiferous tubules of mice treated with lead acetate. Thirty BALB/c mice (Mus musculus) were divided into 5 groups. Group N was the negative control group with no treatment. Group P was the positive control group, which was given 0.075 g/kgBW of lead acetate once in a day for 35 days. The treatment groups, T1, T2 and T3, were treated with curcumin 100, 200 and 400 mg/kg BW once a day for 3 days; after 3 days, they were treated with curcumin 100, 200 and 400 mg/kg BW; then, 1 h later, they were treated with lead acetate 0.075 g/kg BW once a day for 35 days. There was a significant difference in epithelial thickness of seminiferous tubule between group P and group T3, and a significant difference in the diameter of seminiferous tubules between group P and groups T2 and T3. Curcumin dosages of 200 and 400 mg/kgBW could significantly maintain the diameter of seminiferous tubules, and curcumin dosage of 400 mg/kgBW could significantly maintain the epithelial thickness of seminiferous tubules of mice treated with lead acetate. HIGHLIGHTS Curcumin as an antioxidant plays an important role in reducing lead toxicity Administration of curcumin could increase the diameter and epithelial thickness of seminiferous tubules, as well as the testicular weight. It was proven that curcumin reduced apoptosis activity by, among others, chelating with lead and serving as a ROS (reactive oxygen species) scavenger Our research found the best dosages of curcumin that could significantly maintain the diameter and epithelial thickness of seminiferous tubules of mice treated with lead acetate GRAPHICAL ABSTRACT